Normative compliance on taxes on profits reported by stock market companies under IFRS - Vilchez Olivares, Percy Antonio (2019)
Objective: To evaluate the level of regulatory compliance of the International Financial Reporting Standards IFRS with respect to the application of International Accounting Standards IAS 12 Income tax on the financial information reported and published by companies listed on the Lima Stock Exchange for the period ended in 2016. Method: It is a practical, descriptive, quantitative and non-experimental research, with numerical data processing through statistical analysis. Results: The sample consisted of 52 companies from the industrial, mining and public service strata. Their frequencies of compliance with financial information under IFRS were reviewed and it was determined that the companies that report their financial information do not comply a 100% with the regulations proposed by the IAS 12 Income tax. Conclusions: The financial information prepared under IFRS and reported by industrial, mining and public service companies has a high propensity to comply with the normative criteria of IAS 12 Income tax with respect to the presentation and disclosure of tax information to earnings.